Evaluasi Aktivitas Manual Material Handling dan Penerapan K3 Bagian Palletizing Kemasan Jerigen di PT. XYZ - Kusnadi, Kusnadi; Hadining, Aulia Fashanah; Wahyudin, Wahyudin (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2020)
Production results that are handled manually are lifting the burden of jerry cans weighing 24 kg from the conveyor to the pallet. This removal process is risky for musculoceletal and can cause lower back pain. The appointment process takes place in the packing line section D. The purpose of this study is to determine the level of risk, find out the form of conveyor in accordance with working conditions and provide recommendations for corrective actions to be taken when the operator's work attitude has the risk of injury. The assessment of work posture is based on the assessment of RULA for each part (upper arm, forearm, wrist, wrist rotation, back, neck, and leg position) which are then categorized based on the results of the grand score on the action level indicating that the posture is required repair or not. The results of this study found that 3 workers for the grand score of work posture an average of 7 which indicates the need for action now. This is influenced by heavy loads with manual lifting.